Multilingualism and Bilingualism in Javanese Society - Nanik Sri Rahmini (Metaphor, 2019)
This study aims at analyzing the case study of multilingualism and bilingualism in three provinces in Java, among others are East Java, Yogyakarta, and Central Java. The people from the three provinces communicate with two or more than languages which causes double-overlapping diglossia phenomenon. The diglossia phenomenon happens in the use of language spoken by the majority and minority people lived in the provinces. This study is qualitative study. The data is collected through library research and the language observation in the field. The study shows that the language shift from Javanese to Bahasa Indonesia happens in the Javanese society. Kromo Inggil is rarely used by the society. They tend to shift the language by speaking Bahasa Indonesia for their daily conversation. However, the Javanese language is used in the way the family members communicate each other with their immediate family. Hence, Javanese language can be insured that it will be used by the next generations.